Who gets medication-assisted treatment for opioid use disorder, and does it reduce overdose risk? Evidence from the Rhode Island all-payer claims database - Mary A. Burke; Riley Sullivan; Katherine Grace Carman; Hefei Wen; J. Frank Wharam; Hao Yu (Federal Reserve Bank of Boston, 2021)
Medication-assisted treatment (MAT) for opioid use disorder (OUD) consists of administering methadone, buprenorphine, or naltrexone in conjunction with behavioral therapy. Despite strong support in the medical and public health communities for MAT, fewer than 10 percent of US patients with diagnosed OUD receive this treatment, according to some estimates. Rhode Island has adopted robust and innovative policies to promote comprehensive care for OUD that includes MAT, and the available evidence suggests that the state has an above-average rate of MAT uptake; nevertheless, the opioid-related mortality rates in Rhode Island-and on average in the United States-remain elevated. This situation prompts questions about the ability of recent policy measures to achieve sufficient increases in the uptake of MAT and about the practical efficacy of MAT in reducing overdose risk. Using the all-payer claims database for Rhode Island (known as HealthFacts RI), this paper studies (1) the effectiveness of MAT as practiced in Rhode Island in preventing opioid overdoses, (2) the factors at the patient level that either inhibit or facilitate the uptake of MAT, and (3) the impact that federal policies implemented in 2016 have had on buprenorphine prescribing patterns in Rhode Island.
Keywords: I18; I13; I14; I12; 330; medication-assisted treatment; opioid use disorder; Rhode Island; all-payer claims database; methadone; buprenorphine; overdose; Opiate; Medizinische Behandlung; Rhode Island; USA (Ostküste)